KELAYAKAN MEDIA PEMBELAJARAN MACROMEDIA FLASH 8 MULTIPLE INTELLIGENCES KELAS IV SD - Jois Syahadati Masruriyah; Galih Istiningsih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is focused on the lack of students' mathematical communication in learning mathematics, especially in the length of the material unit. In addition, this article discusses a study about the feasibility of a learning media, namely "Macromedia flash MI", which is considered to provide convenience for students in understanding the material. The study is based on the feasibility of Macromedia Flash MI media in the length material unit for fourth-grade students in mathematics learning at SDN Danupayan. The study used research and development methods (Research and Development) and was conducted in the academic year of 2021/2022. The subject of the study was the fifth-grade students in one of the Elementary Schools in Bulu Temanggung. The media validation or the feasibility test of media showed a percentage of 97.2%, which could be concluded that the media validity showed the Very Valid (SV) category with an interval between the percentages of 81.25%–100%. The data was obtained from 3 validators, they were one lecturer at the Universitas Muhammadiyah Magelang and two teachers at one of the Elementary Schools in Bulu Temanggung. Subsequently, the results of the research on student responses to the media showed a percentage of 82.16%, which could be concluded that the validity of the media showed the Very Valid (SV) category with an interval between the percentages of 81.25-100%. The data were obtained from the questionnaire data and collected from 6 respondents. Thus, MI Macromedia Flash media was suitable for use in learning.